Analytical specificity and sensitivity of the novel dual‐target GeneProof Neisseria gonorrhoeae PCR kit for detection of N. gonorrhoeae. Issue 11 (2nd September 2015) - Golparian, Daniel; Hellmark, Bengt; Unemo, Magnus
<x xml:space="preserve">Abstract</x> Detection of Neisseria gonorrhoeae relies increasingly on nucleic acid amplification tests (NAATs). The specificity of many gonococcal NAATs has been suboptimal and supplementary testing remains recommended in Europe and several additional countries. The novel dual‐target GeneProof Neisseria gonorrhoeae PCR kit, targeting porA pseudogene and 16S rRNA gene, showed a high specificity and sensitivity when isolates of non‐gonococcal Neisseria and related species (n = 144), and gonococci (n = 104) were tested. However, rare gonococcal porA mutants were only detected in the 16S rRNA gene target and two non‐gonococcal isolates showed a low‐level cross‐reactivity in the 16S rRNA gene target. The detection limit for both targets was 1.5 copies per reaction.